REPRESENTASI KEKECEWAAN PEREMPUAN PADA CERPEN “PEREMPUAN YANG MENIKMATI TUBUHNYA SENDIRI” KARYA M. RIFDAL AIS ANNAFIS - Sucipto, Hanna Aulia Rahmah; Nabila, Jihan; Vinindika, Nabila; Nugraha, Robby; Harini, Yostiani Noor Asmi (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2024)
This study aims to describe the representation of women's disappointment in the structure of short story texts. The theories used in this study are structural theory by Levi-Strauss and literary sociological theory by Damono with the originator of Ian Watt's theory. This study uses qualitative descriptive method by analyzing the relationship between short stories and social reality. The short story "The Woman Who Marries Her Own Body" was examined through data collection steps: (1) reading the short story "The Woman Who Marries Her Own Body" intensively; (2) analyze interinsic and external elements; (3) describe the representation of women's disappointment in the structure of the short story text. The results of this research by reading, analyzing, and describing the relationship show a representation of Asti's disappointment as the main character in the short story with a structural theory and literary sociology approach that represents the reality of the perpetrators of crimes who have acted criminally on women and minors and this deviation from norms makes the main character represent her trauma and disappointment by marrying her own body.